2014
DOI: 10.1007/s11295-014-0803-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping and validation of QTLs associated with resistance to Calonectria leaf blight caused by Calonectria pteridis in Eucalyptus

Abstract: Calonectria leaf blight (CLB) caused byCalonectria pteridis is one of the main leaf diseases in Brazilian Eucalyptus plantations in warm climates with prolonged periods of rain. The main symptoms are leaf spots followed by intense defoliation in highly susceptible plants.Exploiting the existing inter-and intraspecific variability for defoliation is the best option to control this disease. Nevertheless, nothing is known about the genetic architecture of resistance to CLB in Eucalyptus. We built microsatelliteba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 28 publications
0
14
1
Order By: Relevance
“…This isolate is highly aggressive to eucalypt and has been used in the evaluation of resistance of Corymbia, Eucalyptus species and hybrids (Alfenas et al, 2016;Zarpelon et al, 2015). Disks from the monospore culture of the fungus were transferred to Petri dishes containing ODA medium (7% oat, 2% dextrose and 2% agar).…”
Section: Inoculum Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…This isolate is highly aggressive to eucalypt and has been used in the evaluation of resistance of Corymbia, Eucalyptus species and hybrids (Alfenas et al, 2016;Zarpelon et al, 2015). Disks from the monospore culture of the fungus were transferred to Petri dishes containing ODA medium (7% oat, 2% dextrose and 2% agar).…”
Section: Inoculum Preparationmentioning
confidence: 99%
“…Dissemination of fungal spores is mainly by wind (Mohanty, Pandey, Arya, & Harsh, 2012). The planting of resistant clones is the most efficient and economical method for CLB control in eucalypt plantations Crous, 2002;Zarpelon et al, 2015). The planting of resistant clones is the most efficient and economical method for CLB control in eucalypt plantations Crous, 2002;Zarpelon et al, 2015).…”
mentioning
confidence: 99%
“…Authors identified QTLs for Eucalyptus traits, such as growth, disease resistance and wood properties (GRATTAPAGLIA et al, 1996;THAMARUS et al, 2004;THUMMA et al, 2010;ZARPELON et al, 2015). However, for selection purposes, QTLs have not shown good results for traits with low h² (RESENDE et al, 2008).…”
Section: Eucalyptus Breeding History In Brazilmentioning
confidence: 99%
“…Recently, five Quantitative Trait Loci associated with resistance to CLB in Eucalyptus urophylla x E. camaldulensis (EU11 × EC06) were detected by Zarpelon et al. () providing a starting point for future studies of the genetics of resistance to CLB.…”
Section: Introductionmentioning
confidence: 99%
“…The use of resistant genotypes is the best method for CLB control, because observations in the field under natural infection and results of inoculations under controlled conditions indicate the existence of inter-and intraspecific variability for resistance in eucalypt Fonseca et al 2010). Recently, five Quantitative Trait Loci associated with resistance to CLB in Eucalyptus urophylla x E. camaldulensis (EU11 9 EC06) were detected by Zarpelon et al (2015) providing a starting point for future studies of the genetics of resistance to CLB.…”
Section: Introductionmentioning
confidence: 99%